Sprint interval climbing increases anaerobic training load in elite female +78 kg judo athletes - Huang, L.; Yao, H.; Weng, X.; Chen, H. (Frontiers in Sports and Active Living, 2025)
Introduction: The decisive movements that determine judo performance rely on anaerobic power. Currently, the optimum training protocol for increasing the anaerobic endurance of heavyweight judo athletes remains elusive due to tricky balance between training loads increase and injury prevention. This study investigated the impact of sprint interval climbing incorporated into the regular training on the anaerobic training load of heavyweight judo athletes.